2009
DOI: 10.1007/s00330-009-1302-0
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling of the aortic root in severe tricuspid aortic stenosis: implications for transcatheter aortic valve implantation

Abstract: Remodelling of the aortic root in severe tricuspid aortic stenosis: implications for transcatheter aortic valve implantation Abstract Detailed knowledge of aortic root geometry is a prerequisite to anticipate complications of transcatheter aortic valve (TAV) implantation. We determined coronary ostial locations and aortic root dimensions in patients with aortic stenosis (AS) and compared these values with normal subjects using computed tomography (CT). One hundred consecutive patients with severe tricuspid AS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 35 publications
(45 reference statements)
5
33
0
Order By: Relevance
“…In contrast, Stolzmann et al reported that transverse, but not longitudinal, remodeling of the aortic root, including increased diameter of the aortic annulus and sinotubular junction, occurs in patients with severe AS. 20 Although further studies are needed to resolve these conflicting results, the wide intersubject variability and reduced distance to the coronary arteries raises the importance of these measurements before TAVI. Our results suggest that 3DTEE may be a potential alternative to MDCT for assessing aortic root geometry.…”
Section: Current Studymentioning
confidence: 99%
“…In contrast, Stolzmann et al reported that transverse, but not longitudinal, remodeling of the aortic root, including increased diameter of the aortic annulus and sinotubular junction, occurs in patients with severe AS. 20 Although further studies are needed to resolve these conflicting results, the wide intersubject variability and reduced distance to the coronary arteries raises the importance of these measurements before TAVI. Our results suggest that 3DTEE may be a potential alternative to MDCT for assessing aortic root geometry.…”
Section: Current Studymentioning
confidence: 99%
“…For a successful TAVI procedure, certain anatomic criteria must be met to facilitate valve delivery and placement. Due to the large inter-individual differences concerning the location of the coronary ostia and the dilatation of the aortic root in patients with aortic stenosis, pre-procedural cardiac CT seems advisable [15]. Injury to the femoral or iliac arteries during valve delivery via a large introducer sheath is of major concern, consequently patient selection is critical.…”
Section: Introductionmentioning
confidence: 98%
“…Accurate knowledge of the anatomy of the aortic valveaortic root complex as well as precisely locating the coronary ostia is critical for a number of interventional and surgical cardiovascular procedures, including cannulation or catheterization of the coronary arteries, aortic graft repair or root replacement, and implantation of aortic valves using minimal invasive surgical or interventional techniques [1]. In addition, detailed visualization of the anatomy is mandatory for demonstrating the extent of aortic disease involving the aortic root, such as type A aortic dissection or annulo-aortic ectasia and aortic aneurysms.…”
Section: Introductionmentioning
confidence: 99%